Transport and accumulation of ferrocene tagged poly(vinyl chloride) at the buried interfaces of plasticized membrane electrodes - Manzar, S.; De Marco, Roland; Alam, M.; Pawlak, Marcin; Bakker, Eric (Royal Society of Chemistry, 2013)
Cyclic voltammetry (CV), synchrotron radiation-X-ray photoelectron spectroscopy (SR-XPS) and near edge X-ray absorption fine structure (NEXAFS) show that oxidation of ferrocene tagged PVC induces an accumulation of high molecular weight polymer at the buried interface between the substrate electrode and the plasticized membrane.